A chemical speciation insight into the palladium(ii) uptake and metabolism by Sinapis alba. Exposure to Pd induces the synthesis of a Pd–histidine complex. Issue 9 (7th August 2019) - Kińska, Katarzyna; Bierla, Katarzyna; Godin, Simon; Preud'homme, Hugues; Kowalska, Joanna; Krasnodębska-Ostręga, Beata; Lobinski, Ryszard; Szpunar, Joanna
Abstract : The metabolism of Pd by Sinapis alba – the biosynthesis of a Pd–histidine complex as a result of metal stress. Abstract : Palladium is recognized as a technologically critical element (TCE) because of its massive use in automobile exhaust gas catalytic converters. The release of Pd into the environment in the form of nanoparticles of various size and chemical composition requires an understanding of their metabolism by leaving organisms. We provide here for the first time a chemical speciation insight into the identity of the ligands produced or used by a plant Sinapis alba L . exposed in hydropony to Pd nanoparticles and soluble Pd (nitrate). The analytical method developed was based on the concept of 2D HPLC with parallel inductively coupled plasma mass spectrometry (ICP MS) and electrospray MS detection. Size exclusion chromatography – ICP MS of the plant extracts showed no difference between the speciation of Pd after the exposure to nanoparticles and after that to Pd 2+ which indicated the reactivity and dissolution of Pd nanoparticles. A comparative investigation of the Pd speciation in a control plant extract spiked with Pd 2+ and of an extract of a plant having metabolized palladium indicated the response of the Sinapis alba by the formation of a Pd–histidine complex. The complex was identified via Orbitrap MS; the HPLC-MS chromatogram produced two peaks at m / z 415.0341 each corresponding to a Pd–His2 complex. An investigation by ion-mobility MS revealed a difference in their collision cross section indicating that the complexes present varied in terms of spatial conformation. A number of other Pd complexes with different ligands (including nicotianamine) circulating in the plant were detected but these ligands were already observed in a control plant and their concentrations were not affected by the exposure to Pd.